Handgrip Strength Asymmetry and Weakness Together Are Associated With Functional Disability in Aging Americans. (22nd April 2020) - McGrath, Ryan; Vincent, Brenda M; Jurivich, Donald A; Hackney, Kyle J; Tomkinson, Grant R; Dahl, Lindsey J; Clark, Brian C
Abstract: Background: Evaluating handgrip strength (HGS) asymmetry may help to improve the prognostic value of HGS. This study sought to determine the associations of HGS asymmetry and weakness on future activities of daily living (ADL) disability in a national sample of aging Americans. Methods: The analytic sample included 18, 468 Americans aged ≥50 years from the 2006–2016 waves of the Health and Retirement Study. A handgrip dynamometer measured HGS. Those with HGS >10% stronger on either hand were considered as having any HGS asymmetry. Individuals with HGS >10% stronger on their dominant hand were considered as having dominant HGS asymmetry, while those with HGS >10% stronger on their nondominant hand were classified as having nondominant HGS asymmetry. Men with HGS <26 kg and women with HGS <16 kg were considered weak. ADLs were self-reported. Generalized estimating equations were used for analyses. Results: Relative to those with symmetric HGS and no weakness, each HGS asymmetry and weakness group had increased odds for future ADL disability: 1.11 (95% confidence interval [CI]: 1.02–1.20) for any HGS asymmetry alone, 1.42 (CI: 1.16–1.74) for weakness alone, and 1.81 (CI: 1.52–2.16) for both any HGS asymmetry and weakness. Most weakness and HGS asymmetry dominance groups had increased odds for future ADL disability: 1.30 (CI: 1.13–1.50) for nondominant HGS asymmetry alone, 1.42 (CI: 1.16–1.74) for weakness alone, 1.72 (CI: 1.29–2.29) for both weakness and nondominant HGS asymmetry, and 1.86 (CI: 1.52–2.28) for both weakness and dominant HGS asymmetry. Conclusions: HGS asymmetry and weakness together may increase the predictive utility of handgrip dynamometers.